Assessment of performance enhancement of a semi-submersible vertical axis wind turbine with an optimized Darrieus rotor. (15th July 2018) - Cheng, Zhengshun; Wang, Kai; Ong, Muk Chen
Highlights: Performance enhancement of a semi-submersible VAWT due to an optimized rotor is assessed. Numerical simulations are conducted by a fully coupled aero-hydro-servo-elastic code. The optimized rotor improves the performances with respect to power production, global motion, mooring line tension. The variation of tower base bending moments is greatly reduced, causing less fatigue damage. Abstract: Increasing efforts are currently being devoted to develop floating vertical axis wind turbines (VAWTs), due to their potential to reduce the cost-of-energy. Optimization of rotors is favorable to increase the power capture and mitigate structural loads. In the DeepWind project, a baseline Darrieus type vertical axis wind turbine (VAWT) was first developed, followed by an optimized rotor. In this study, these two different rotors are adapted to a semi-submersible platform to achieve two floating VAWTs. The performance enhancement of the floating VAWT with the optimized rotor is evaluated by performance comparison with the floating VAWT with the baseline rotor. Numerical simulations are conducted using a fully coupled aero-hydro-servo-elastic simulation tool in time domain, under turbulent wind and irregular waves. Numerical analyses indicate that the floating VAWT with the optimized rotor greatly improves the performances with respect to power production, global platform motions, mooring line tensions, and especially tower base bending moments. The annual power production of the floating VAWT with the optimized rotor is improved by 11.3% as compared to that of the floating VAWT with the baseline rotor. However, the variations of flapwise and edgewise bending moments along the blades are not improved for the optimized rotor, which might cause severe fatigue damage, and should be considered during the optimization of blades for VAWTs.